2016
DOI: 10.1128/mbio.00347-16
|View full text |Cite|
|
Sign up to set email alerts
|

Sequential Acquisition of Virulence and Fluoroquinolone Resistance Has Shaped the Evolution of Escherichia coli ST131

Abstract: Escherichia coli ST131 is the most frequently isolated fluoroquinolone-resistant (FQR) E. coli clone worldwide and a major cause of urinary tract and bloodstream infections. Although originally identified through its association with the CTX-M-15 extended-spectrum β-lactamase resistance gene, global genomic epidemiology studies have failed to resolve the geographical and temporal origin of the ST131 ancestor. Here, we developed a framework for the reanalysis of publically available genomes from different count… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
194
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(213 citation statements)
references
References 39 publications
11
194
2
Order By: Relevance
“…2. The tree comprises three clades (A, B, and C) and four subgroups (C0, C1, C1-M27, and C2) within clade C, findings consistent with previous studies (13,14). Among the STC131 strains detected in the present study, four strains belonged to clade A and 11 strains belonged to clade C. Congruent with previous studies, strains belonging to clade C were characterized by the fimH30 allele and LNIV (S83L and D87N in GyrA and S80I and E84V in ParC) genotypes in QRDRs.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…2. The tree comprises three clades (A, B, and C) and four subgroups (C0, C1, C1-M27, and C2) within clade C, findings consistent with previous studies (13,14). Among the STC131 strains detected in the present study, four strains belonged to clade A and 11 strains belonged to clade C. Congruent with previous studies, strains belonging to clade C were characterized by the fimH30 allele and LNIV (S83L and D87N in GyrA and S80I and E84V in ParC) genotypes in QRDRs.…”
Section: Resultssupporting
confidence: 80%
“…H41, H22, and H30 indicate the fimH (type 1 fimbrial adhesin gene) allele type, and most strains belonging to each clade are known to carry the corresponding fimH allele. Clade C contains C0, C1, and C2, which can be defined based on the positions in the whole-genome phylogeny (13). Previous studies reported that the bla CTX-M-15 -harboring C2/H30Rx is highly responsible for the pandemic of ExPEC strains that carry ESBLs (9,11,12).…”
mentioning
confidence: 99%
“…Recent studies focusing on evolutionary history of ST131 suggested that C1/ H 30R and C2/ H 30Rx clades emerged ≈30 years ago, after their acquisition of gyrA -1AB and parC -1aAB alleles from C0/ H 30 (non-R) clade ( 27 , 28 ). The phylogeny and smaller numbers of SNPs in the C1-M27 clade (Figure 1) suggest that this clade was recently diverged from the C1/ H 30R.…”
Section: Discussionmentioning
confidence: 99%
“…According to the work of Ben Zakour et al [7], we determined the subclade B type of H 22 strain S250 and the clade C type of strain JJ1886 by direct blasting of the genes of the Flag-2 locus (Flag-2 locus from strain E. coli 042 [EMBL: CR 753847]), Phi3 (from strain EC958), and GI-PheV (from strain JJ1886) against the genome of strains S250 and JJI886. We then determined the type of subclade B displayed by strain S250 and the two other fecal H 22 strains by PCR using primers specific for the Flag-2 locus, Phi3, and GI-PheV (Additional file 1: Table S1) and our H 30-R fecal strains as a positive control.…”
Section: Methodsmentioning
confidence: 99%
“…It also revealed that subclone H 22 was the precursor of subclone H 30 and that separate F-type plasmids have shaped the evolution of subclone H 30 [2, 3, 5, 6]. The most recent ST131 E. coli phylogenetic reconstruction carried out by Ben Zakour et al using 3779 non-recombinant single nucleotide polymorphisms (SNP) found in the high quality genomes of 172 clade B and C strains, identified five B subclades, for which the independent evolutionary trajectories are characterized by successive insertions and a recombination from ancestral H 22 (subclade B1) [7]. Subclade B2 is characterized by a Flag-2 locus insertion, subclade B3 by a Flag-2 locus insertion and par-C2 recombination, subclade B4 by Flag-2 locus and GI-PheV insertions, and subclade B5 by Flag-2 locus and Phi3 insertions.…”
Section: Introductionmentioning
confidence: 99%